EFEKTIVITAS LIMBAH CAIR PERTANIAN SEBAGAI MEDIA PERBANYAKAN DAN FORMULASI Bacillus subtilis SEBAGAI AGENS HAYATI PATOGEN TANAMAN - Khaeruni, Andi; Asrianti, Asrianti; Rahman, Abdul (Jurnal Agroteknos, 2013)
This study aimed to find the best medium for formulation and storage of B. subtilis. The study consisted of two phases: (1) Selection of agricultural wastes as a propagation medium for Bacillus subtilis, (2) test for the stability of Bacillus subtilis in material formulation and its inhibition activity against Rhizoctonia solani. The second phase was conducted based on completely randomized design, consisting of five treatments, namely: 100 % medium synthetic, 100% coconut water, 75% coconut water + 25 % synthetic medium, 50% coconut water + 50% synthetic medium and 25% coconut water + 75% synthetic medium. Each treatment was repeated three times, so that there were 15 experimental units. B. subtilis ST21e isolate was formulated in liquid medium according to treatment and kept in plastic container at room temperature for 8 weeks to count the number of colonies and inhibition activity every 2 weeks. The results showed that the agricultural wastes (coconut water, tofu water and molasses) can be used as a media for B. subtilis ST21e propogation in different cell growth pattern. B. subtilis propogation in medium coconut water + 10% TSB had the best growth pattern compared to the other media. On the other hand, medium containing 25% coconut water + 75% synthetic medium was the best combination for storage medium of B. subtilis ST21e. Key words: biological agents, Bacillus subtilis, agricultural waste